PEMANFAATAN TEKS MULTIMODAL SEBAGAI INOVASI MATERI PEMBELAJARAN BAHASA INDONESIA PADA MASA PANDEMI COVID-19 (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
Abstract Based on the 2013 Curriculum, Indonesian language learning in SMP is text-based. During this pandemic, learning various texts should take advantage of existing technology with teaching materials in the form of multimodal texts. This study aims to describe the use of multimodal text as an innovation in Indonesian language learning materials in junior high schools and the implementation of learning. This study used descriptive qualitative method. Data collection techniques using observation techniques, interviews, documents, and audiovisual materials. Observation and document techniques were used to observe and document the textbooks used in Indonesian language learning for grade VIII SMP, both from offline and online data. Audiovisual techniques to collect data in the form of multimodal text sourced from the internet and social media. The data validity used data triangulation techniques, researchers, methods, and theories. The data analysis technique was done by reducing the data, presenting the data, and concluding. The results showed that multimodal text learning as an innovation in Indonesian language learning materials in class VIII SMP was beneficial for students to improve their literacy competencies in the era of the industrial revolution 4.0. In addition, it can also introduce students to types of text that are broader, more eye-catching, and less saturating. Students and teachers can explore these materials from the internet or social media in accordance with the teaching material. The teacher must prepare a good and appropriate lesson plan and scenario. Keywords: multimodal text; Indonesian language teaching materials; learning media